2009
DOI: 10.1038/ki.2009.116
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive Bardet–Biedl syndrome: first-degree relatives have no predisposition to metabolic and renal disorders

Abstract: Bardet-Biedl Syndrome (BBS) is an autosomal recessive, multisystem, genetically heterogeneous, ciliopathic condition caused by mutations in multiple genes. Here we sought to determine if inheritance of a single BBS mutation increased the risks of frequent disorders of this syndrome such as obesity, hypertension, and diabetes. Various metabolic and renal diseases in a cohort of 46 patients with BBS, prospectively followed for up to 28 years, were compared to recent assessments of these factors in 96 relatives w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
1
20
1
Order By: Relevance
“…The dominant-negative model may explain the increased incidence of heterozygous BBS gene mutation carriers in patients with BBS syndrome as well as the role of single-copy gene alterations in triallelic inheritance [Fauser et al, 2003;Hichri et al, 2005;Hjortshøj et al, 2010]. Some reports indicate an increased incidence of isolated BBS-related symptoms in parents of BBS patients and/or heterozygous carriers of the BBS gene mutations, while other studies disagree with this statement [Croft et al, 1995;Beales et al, 1999;Cox et al, 2003;Hjortshøj et al, 2007;Kim et al, 2007;Webb et al, 2009].…”
Section: %mentioning
confidence: 70%
“…The dominant-negative model may explain the increased incidence of heterozygous BBS gene mutation carriers in patients with BBS syndrome as well as the role of single-copy gene alterations in triallelic inheritance [Fauser et al, 2003;Hichri et al, 2005;Hjortshøj et al, 2010]. Some reports indicate an increased incidence of isolated BBS-related symptoms in parents of BBS patients and/or heterozygous carriers of the BBS gene mutations, while other studies disagree with this statement [Croft et al, 1995;Beales et al, 1999;Cox et al, 2003;Hjortshøj et al, 2007;Kim et al, 2007;Webb et al, 2009].…”
Section: %mentioning
confidence: 70%
“…According to different reports, they should be at risk of developing obesity, hypertension, retinal dysfunction, and renal cancers and abnormalities [72][73][74][75]. However, this risk was not confirmed by two large studies comparing BBS relatives with or without a heterozygous mutation [76,77].…”
Section: Clinical Expression Of the Disease In Heterozygous Carriersmentioning
confidence: 72%
“…It is of interest to note that in a group of older patients, O'Dea et al pointed out that 100% of their patients with BBS had renal structural abnormalities and 25% had impaired GFR by the age of 48 years (24). In the same way, Webb et al recently reported a Newfoundland series of BBS with a prevalence of CKD stage 3 (eGFR Ͻ60 ml/min per 1.73 m 2 ) reaching 47% (20 of 43) at a median age onset of CKD of 58 years (25). Stage 4 CKD (eGFR Ͻ30 ml/min per 1.73 m 2 ) concerned 20% of patients and 14% progressed to ESRD.…”
Section: Discussionmentioning
confidence: 90%